2019
DOI: 10.3847/1538-3881/ab3e04
|View full text |Cite
|
Sign up to set email alerts
|

Two Long-period Cataclysmic Variable Stars: ASASSN-14ho and V1062 Cyg

Abstract: We report spectroscopy and photometry of the cataclysmic variable stars ASASSN-14ho and V1062 Cyg. Both are dwarf novae with spectra dominated by their secondary stars, which we classify approximately as K4 and M0.5, respectively. Their orbital periods, determined mostly from the secondary stars' radial velocities, proved to be nearly identical, respectively 350.14 ± 0.15 and 348.25 ± 0.60 min. The Hα emission line in V1062 Cyg displays a relatively sharp emission component that tracks the secondary's motion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…It has been already observationally known such a secondary is indeed present (Thorstensen 2015). Although such a result was apparently not present in model parameters in Knigge (2006) as stated in Gasque et al (2019), studies have shown that such systems can be formed if mass transfer occurs after the secondary has undergone significant nuclear evolution (e.g. Podsiadlowski et al 2003;Goliasch and Nelson 2015).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been already observationally known such a secondary is indeed present (Thorstensen 2015). Although such a result was apparently not present in model parameters in Knigge (2006) as stated in Gasque et al (2019), studies have shown that such systems can be formed if mass transfer occurs after the secondary has undergone significant nuclear evolution (e.g. Podsiadlowski et al 2003;Goliasch and Nelson 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Quite recently, Gasque et al (2019) reported a radial velocity study of this object and obtained P orb of 0.24315(10) d. From the mass function, Gasque et al (2019) derived a constraint on the masses of the primary, secondary and the inclination. Their result favored a massive (∼1.0 M ⊙ ) white dwarf and an undermassive secondary for this P orb .…”
Section: Asassn-14homentioning
confidence: 99%
“…This object showed four rebrightenings after the main superoutburst in 2014 (Kato 2020). The orbital period and mass ratio are 0.24315(10) d and 0.28, respectively (Gasque et al 2019). This orbital period is the longest one among known SU UMa-type DNe.…”
Section: Introductionmentioning
confidence: 77%
“…In Figure 13, we compare the objects in our sample to these objects, and to the canonical donor sequence for unevolved donors (black dashed line). The other objects are QZ Ser (Thorstensen et al 2002a), EI Psc (also called 1RXS J232953.9+062814; Thorstensen et al 2002b), SDSS J170213.26 + 322954.1 (Littlefair et al 2006, BF Eridani (Neustroev & Zharikov 2008), CSS J134052.0 + 151341 (Thorstensen 2013), HS 0218+3229 (Rodríguez-Gil et al 2009), SDSS J001153.08-064739.2 (Rebassa-Mansergas et al 2014, ASAS-SN 13cl (Thorstensen 2015), ASAS-SN 15cm (Thorstensen et al 2016), ASAS-SN 14ho (Gasque et al 2019), V1460 Her (Ashley et al 2020, and ASAS-SN 18aan (Wakamatsu et al 2021). To our knowledge, this represents a near-complete inventory of currently known evolved CV donors, though new systems are regularly being discovered.…”
Section: Comparison To Other Evolved Cvsmentioning
confidence: 99%